(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Combat training for cadets is a rigorous process that demands not only physical endurance but also significant psychological resilience. The high-stress environment of combat training, characterized by intense physical demands, simulated combat scenarios, and time-sensitive decision-making, places unique psychological challenges on cadets. Effective psychological adaptation and coping strategies are critical for cadets to manage stress, maintain mental health, and enhance performance. This article explores the importance of psychological adaptation, the role of coping mechanisms, and their impact on cadets’ success in combat training. By examining stress management techniques, resilience-building programs, and the psychological demands of training, this study underscores the need for integrated mental health support in military education.